Design and experimental research of air-assisted nozzle for pesticide application in orchard - Ou, Mingxiong; Zhang, Jiayao; Du, Wentao; Wu, Minmin; Gao, Tianyu; Jia, Weidong; Dong, Xiang; Zhang, Tie; Ding, Suming (Frontiers in Plant Science, 2024)
This article reports the design and experiment of a novel air-assisted nozzle for pesticide application in orchard. A novel air-assisted nozzle was designed based on the transverse jet atomization pattern. This article conducted the performance and deposition experiments and established the mathematical model of volume median diameter (D50) and liquid flow rate with the nozzle design parameters. The D50 of this air-assisted nozzle ranged from 52.45 μm to 113.67 μm, and the liquid flow rate ranged from 142.6 ml/min to 1,607.8 ml/min within the designed conditions. These performances meet the low-volume and ultra-low-volume pesticide application in orchard. The droplet deposition experiment results demonstrated that the droplet coverage distribution in different layers and columns is relatively uniform, and the predicted value of spray penetration (SP) numbers SPiA, SPiB, and SPiC (i = 1, 2, and 3) are approximately 70%, 60%, and 70%, respectively. The droplet deposits on the foliage of the canopy (inside and outside) uniformly bring benefit for plant protection and pesticide saving. Compared with the traditional air-assisted nozzle that adopts a coaxial flow atomization pattern, the atomization efficiency of this air-assisted nozzle is higher. Moreover, the nozzle air pressure and liquid flow rate are considerably lower and greater than the traditional air-assisted nozzle, and these results proved that this air-assisted nozzle has great potential in orchard pesticide application. The relationship between the D50 and nozzle liquid pressure of this air-assisted nozzle differs from that of traditional air-assisted nozzles due to the atomization pattern and process. While this article provides an explanation for this relationship, further study about the atomization process and mechanism is needed so as to improve the performance.